Interpreting the Pauline Epistles - Schreiner, Thomas R. (Grand Rapids, Mich. : Baker Academic, 2011)
Thomas Schreiner provides an updated guide to the exegesis of the New Testament epistles traditionally assigned to Paul. The book helps readers understand the nature of first-century letters, do textual criticism, investigate historical and introductory issues, probe theological context, and more. --from publisher description
Understanding the nature of letters -- Doing textual criticism -- Translating and analyzing the letter -- Investigating historical and introductory issues -- Diagramming and conducting a grammatical analysis -- Tracing the argument -- Doing lexical studies -- Probing the theological context -- Delineating the significance of Paul's letters -- Conclusion -- Select commentaries on the Pauline Epistles.
Originally published: Grand Rapids, Mich. : Baker Book House, c1990, in series: Guides to New Testament exegesis ; 5.
Includes bibliographical references.
Keywords: Bible. -- Hermeneutics